Students’ Perseptions Of Limited Online and Face to Face Biology Learning at SMAN 2 Pekanbaru - Gusniati, Gusniati; Mellisa, Mellisa (Perspektif Pendidikan dan Keguruan, 2022)
This study aims to determine students’ perceptions of the implementation of limited online and face to face biology learning during the Covid-19 Pandemic Class XI IPA SMAN 2 Pekanbaru in the 2021/2022 Academic Year, totaling 75 students. This research a quantitative research. The method used in this study is a survey method. Data was collected using questionnaire distributed consisted of 38 online learning statement items and 38 limited face to face learning statements. Based on the research result, it can be seen that students’ perceptions of the implementation of online biology learning are categorized as good with an average of 73,02% and student’ perceptions of limited face to face biologi learning are categorized as good with an average of 79,01%. Where of the two variable, limited face to face biology learninf has an average of 79,01% higher than online biology learning 73,02%. Students still have difficulty understanding online learning.